LITERATURE REVIEW: ANALISIS PENYEBAB KEJADIAN STUNTING PADA BALITA DI PROVINSI JAWA TIMUR: Literature Review: Analisis Penyebab Kejadian Stunting pada Balita di Provinsi Jawa Timur - Pertiwi, Aisyah Noer Auliyah Madani; Hendrati, Lucia Yovita (Universitas Airlangga, 2023)
Background: The prevalence of stunting in East Java Province in 2022 reached 19.2%, showing a decrease compared to 2021, which recorded a prevalence rate of 23.5%. Despite the declining trend in stunting prevalence in East Java, the province has not yet achieved the Renstra target, which stipulates that the prevalence of stunting should decrease to 18.4% by 2022. Objectives: This study aims to investigate further the causes of stunting incidents in East Java Province. Methods: The method employed in this research is a literature review, where data sources are obtained using the Google Scholar electronic database. The research search process follows the PICOS protocol, formulating keywords using Boolean Operator techniques. The keywords used are